2019
DOI: 10.1021/acssensors.9b01163
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Double-Stranded DNA-Templated Copper Nanoprobes for Rapid Diagnosis of Tuberculosis

Abstract: In this work, we investigate highly sensitive fluorescent Cu nanoparticles for use as rapid and specific nucleic acid amplification nanoprobes (NPs) for the diagnosis of tuberculosis. After applying polymerase chain reaction (PCR) to a tuberculosis (TB) sample, we demonstrate that the presence of the targeted IS6110 DNA sequence of TB can be easily and directly detected through the in situ formation of DNA-templated fluorescent Cu NPs and subsequently quantified using only a smartphone. Compared to traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] Double-stranded DNA (dsDNA) with adjustable sequences and lengths has been considered as a template for the synthesis of fluorescent copper nanoparticles/nanoclusters. [78][79][80][81][82] Moreover, it has been shown that at lower concentrations of metal precursor, Cu 2+ first binds to backbone phosphate groups of DNA via a nonspecific interaction. However, with increasing the concentration, the metallization of high affinity bases is favoured.…”
Section: Bottom-up Synthesis 2121 Template Mediated Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] Double-stranded DNA (dsDNA) with adjustable sequences and lengths has been considered as a template for the synthesis of fluorescent copper nanoparticles/nanoclusters. [78][79][80][81][82] Moreover, it has been shown that at lower concentrations of metal precursor, Cu 2+ first binds to backbone phosphate groups of DNA via a nonspecific interaction. However, with increasing the concentration, the metallization of high affinity bases is favoured.…”
Section: Bottom-up Synthesis 2121 Template Mediated Synthesismentioning
confidence: 99%
“…dsDNA-templated CuNCs have been applied for the diagnosis of tuberculosis (TB). 79 The in situ cluster formation in the presence of PCR product of the targeted IS6110 DNA sequence of TB is only successful if specifically designed AT-rich primers are used. With this, the formation of dimers and other unwanted hairpin structures and their contribution to PL were kept at a minimum level.…”
Section: Infections Detectionmentioning
confidence: 99%
“…Metal nanoclusters (NCs) are ultrasmall nanomaterials (normally < ca. 2 nm), which contain a few atoms of a precise number. The metal NCs interpose between metal nanoparticles (NPs) and the atoms . Traditional metal NPs of large sizes show surface plasmon resonance (SPR) effects, but metal NCs do not support SPR.…”
Section: Unique Metal Nanoclustersmentioning
confidence: 99%
“…After reduction by NaBH 4 , Ag NCs with 1–4 atoms grew on the template, as indicated by mass spectra [57] . Fluorescent Cu NPs have also been fabricated on DNA by sodium ascorbate reduction, and later served as nucleic acid amplification nanoprobes for tuberculosis diagnosis [126] . Silver‐DNA NPs can also be prepared by electrodeposition in which a potential is applied in the presence of DNA and silver precursor [56] .…”
Section: Bio‐templates For the Synthesis Of Mnmsmentioning
confidence: 99%